The Valuation System of the National Land Fund - Czinege, Anikó (Acta Agraria Debreceniensis, 2005)
The aim of establishing a National Land Fund was to realise the rational management of land property belonging to the Hungarian State, to assist in the realisation of estate political directives, and also to support the development of a modern property structure based on family farms. During this 3 years operation the National Land Fund has become the major player of the Hungarian land market. It has arranged land trades totaling 15,000 hectares, which makes 50% of total related turnover. The NLF created the reason for the existence of land as credit security with the provision of security of mortgage credits. National Land Fund has written co-operation contracts with 11 commercial banks in order to provide long-term agricultural mortgage with the background of land security. NLF has issued almost 1,000 conditional declarations of land purchase to the banks, helping the credit system of agricultural companies.The valuation system „TÉR” created by the National Land Fund, is a many-sided, flexible system adjusted to Hungarian conditions. This evaluation system can determine the value of land in a reliable way. NLF built further controls into the process with the co-operation of independent revisers providing real determination of land value.